Increasing Mathematics Learning Outcomes Through The Application of Rule Learning Methods in Class VII Students of SMPN Walenrang, Lamasi District - Jumasliati Jumasliati (Jurnal Konsepsi, 2020)
This research is classroom action research. The research was conducted at the Walenrang State Junior High School, Lamasi District. This study involved students of class VII with a total of 40 students. The purpose of this research is to improve mathematics learning outcomes through the application of the RULE LEARNING method to the seventh grade students of SMP Negeri Walenrang. This study used 2 cycles with each cycle consisting of 5 meetings. Based on the results of the implementation of learning and discussion on the implementation of learning the rule learning method in class VII, the authors can conclude that efforts to increase student activity and involvement in the learning process as well as improve learning outcomes in mathematics can be done by applying the rule learning method. The results of this study prove that the rule learning type learning model is able to improve student learning outcomes in the learning process.